Upaya Guru dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Tahfidz Al-Qur’an di SMP PK Muhammadiyah Al-Kautsar Kartasura - Delia Vialo Lozada; Triono Ali Mustofa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study aims to examine the efforts made by teachers to develop interest in learning Tahfidz Al-Qur’an subjects at SMP PK Muhammadiyah Al-Kautsar Kartasura. Then, it also has the aim of knowing the factors that support and hinder the success of students' interest in learning Tahfidz Al-Qur’an subjects at SMP PK Muhammadiyah Al-Kautsar Kartasura. This research is a qualitative research. The type of research applied is descriptive research. Type of field research through a qualitative approach. The source of this data is obtained from interviews with students in grades VII, VIII, and IX as well as the teacher who teaches the subject of Tahfidz Al-Qur’an Al-Qur'an. Data collection methods through observation, interviews and documentation. Observations carried out by researchers were directly present at SMP PK Muhammadiyah Al-Kautsar Kartasura. The validity test in this study is using triagulation techniques. Data analysis used is the result of data collection, data reduction, data presentation, conclusions and verification. The results of the research are the teacher's efforts in developing students' desire to learn include the use of various learning methods, providing interesting learning resources, personalized coaching, and collaboration with parents. The results of this study can be concluded that the teacher's efforts in increasing students' desire to learn in the subject of Tahfidz Al-Qur’an Al-Qur'an is by implementing methods to develop expertise in memorizing the Qur'an students are carried out with; 1) halaqah method, 2) talaqqi method, 3) takrir method, 4) giving reweard and punishment, and 5) muroja'ah and motivation. Supporting factors for teachers' efforts in developing students' interest in learning the success of memorizing the Qur'an are; 1) teacher skills and expertise, 2) varied and innovative teaching methods, 3) use of technology, and 4) support from parents and family. As for the inhibiting factors, namely; 1) there are students whose reading of the Qur'an is not perfect, 2) lack of student motivation in memorizing the Qur'an, 3) different levels of student memorization, and 4) time management.